PENGEMBANGAN STANDAR DAN PANDUAN ASUHAN KEPERAWATAN BERBASIS SDKI, SLKI, DAN SIKI UNTUK MENINGKATKAN MUTU PRAKTIK KEPERAWATAN - Wisuda, Aris Citra; Suraya, Citra; Oxyandi, Miming Oxyandi; Surahmat, Raden; Andika Sasmita Putra, Muhamad; Husin, Husin; Emiliasari, Dian (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
Improving the quality of nursing practice is a key pillar in delivering high-quality healthcare services. Nursing care standards and guidelines based on the Indonesian Nursing Diagnosis Standards (SDKI), Nursing Outcomes Standards (SLKI), and Nursing Interventions Standards (SIKI) serve as essential frameworks for providing systematic, measurable, and regulation-compliant care. However, the implementation of these standards in healthcare facilities still faces challenges, including limited understanding and the absence of practical and applicable guidelines. This community service initiative aimed to develop and formulate nursing care standards and guidelines based on SDKI, SLKI, and SIKI to enhance nursing practice quality. The program was conducted at Bayung Lencir Regional General Hospital on April 23–24, 2025, through participatory training and a collaborative workshop involving practicing nurses. Evaluation methods included pre- and post-tests and participatory observation. The results showed a significant improvement in participants’ understanding of the application of the three standards, along with the development of draft operational standards and nursing care guidelines ready for clinical use. In conclusion, this activity made a valuable contribution to improving nurses’ competencies and the quality of nursing services through the development of structured, applicable standards aligned with national regulations